Associations between school and neighbourhood ethnic density and physical activity in adolescents: Evidence from the Olympic Regeneration in East London (ORiEL) study. (September 2019) - Berger, Nicolas; Lewis, Daniel; Quartagno, Matteo; Njagi, Edmund Njeru; Cummins, Steven
Abstract: While most adolescents do not achieve the recommended level of physical activity in the UK, the risk of physical inactivity varies across ethnic groups. We investigated whether own-group school and neighbourhood ethnic density can explain ethnic differences in adolescent physical activity. We used longitudinal data from the Olympic Regeneration in East London (ORiEL) study. In 2012, 3106 adolescents aged 11–12 were recruited from 25 schools in East London, UK. Adolescents were followed-up in 2013 and 2014. Own-group ethnic density was measured in 2012–2014 at school-level and in 2011 at neighbourhood-level, and calculated as the percentage of pupils/residents who were of the same ethnic group. Analyses were restricted to White British (n = 382), White Mixed (n = 190), Bangladeshi (n = 337), and Black African groups (n = 251). We estimated adjusted logistic regression models with generalised estimating equations for self-reported walking to school, walking for leisure, and outdoor physical activity. At school-level, there was consistent evidence that own-group ethnic density amplifies ethnic differences in walking to school. For each 10 percentage point increase in own-group ethnic density, there was evidence of increased probability of walking to school in Bangladeshi adolescents (OR = 1.20; 95% CI 1.09–1.31) and decreased probability of walking to school in Black African (OR = 0.58; 95% CI 0.45–0.75) and White Mixed adolescents (OR = 0.51; 95% CI 0.35–0.76). Associations with walking for leisure and outdoor physical activity were in expected directions but not consistently observed in all ethnic groups. At neighbourhood-level, evidence was more restricted. Amplification of ethnic differences was found for walking to school in Bangladeshi adolescents (OR = 1.31; 95% CI 1.14–1.51) and for outdoor physical activity in White British adolescents (OR = 0.85; 95% CI 0.76–0.94). Our results suggest that own-group ethnic density contributes to explaining differences in physical activity by amplifying ethnic differences in some forms of physical activity. Highlights: We find ethnic variations in adolescent physical activity in East London. At school-level, ethnic density amplifies ethnic differences in walking to school. Associations are less consistent for other physical activity outcomes. The evidence is more restricted for neighbourhood-level ethnic density.